2020
DOI: 10.1093/mnras/staa3294
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluating hydrodynamical simulations with green valley galaxies

Abstract: We test cosmological hydrodynamical simulations of galaxy formation regarding the properties of the Blue Cloud (BC), Green Valley (GV) and Red Sequence (RS), as measured on the 4000Å break strength vs stellar mass plane at z = 0.1. We analyse the RefL0100N1504 run of EAGLE and the TNG100 run of IllustrisTNG project, by comparing them with the Sloan Digital Sky Survey, while taking into account selection bias. Our analysis focuses on the GV, within stellar mass log  M⋆/M⊙ ≃ 10 − 11, selected from the bimodal di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 104 publications
0
16
0
Order By: Relevance
“…The formation histories of simulated galaxies inform us about the formation of galaxies in the real Universe. Meanwhile, the level of agreement between observed and simulated populations among the red sequence, blue cloud, and green valley can indicate ways to improve the physical models that drive the formation histories of galaxies in simulations (Trayford et al 2015(Trayford et al , 2017Nelson et al 2018;Angthopo et al 2021).…”
Section: Introductionmentioning
confidence: 95%
“…The formation histories of simulated galaxies inform us about the formation of galaxies in the real Universe. Meanwhile, the level of agreement between observed and simulated populations among the red sequence, blue cloud, and green valley can indicate ways to improve the physical models that drive the formation histories of galaxies in simulations (Trayford et al 2015(Trayford et al , 2017Nelson et al 2018;Angthopo et al 2021).…”
Section: Introductionmentioning
confidence: 95%
“…In spite of this, we found that the simulations reproduce the trends found in observations (Reichard et al 2009), namely that lopsided disks contain more gas, have higher SFRs, lower metallicity, and bluer colors than the rest of the late-type galaxies. If lopsidedness is related to the presence of star-forming, young populations, it is possible that the low fraction of asymmetric galactic disks in IllustrisTNG is caused by the overquenching effect known to exist in these simulations (Angthopo et al 2021). If too many galaxies prematurely stop forming stars in Illus-trisTNG, they are also less likely to generate lopsided stellar distributions.…”
Section: Discussionmentioning
confidence: 98%
“…At lower redshifts, however, it is also possible that the feedback activities of the central black holes may not be the only and main cause of galaxy quenching, since AGNs among galaxy populations of all colors spend their long lifetimes on the weakly accreting phase (see Figure 3). Various hydrodynamical simulations considering AGN-driven quenching also tend to over-produce the quiescent GV galaxies (i.e., GV galaxies with lower specific star-formation rates) compared with the observations (Angthopo et al 2021), which suggests that there may be some additional mechanisms that dominate quenching at low redshifts, e.g., environmental quenching (Schawinski et al 2014;Belfiore et al 2017;Kacprzak et al 2021), halo quenching (Bluck et al 2020, or a modified more complex AGN-driven quenching mechanism such as halo mass threshold and black hole seed mass triggering AGN feedback (Davé et al 2020;Trussler et al 2020;Angthopo et al 2021).…”
Section: Agn Lifetimes In Galaxies Of Different Extinction-corrected ...mentioning
confidence: 92%